KINERJA GURU BERSERTIFIKASI DI SEKOLAH DASAR NEGERI 003 PULAU PADANG KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Chia Pitaloka; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The Performance Of Teachers Certified In Elementary School 003Pulau Padang. The performance of a teacher have a benefit fungtion. To that end, theteacher quality improvement efforts have been made one through the teacher certificationprogram. However, seen here not found a fundamental difference of performance betweenteachers who are not certified by the certification, the low motivation of teachers and, stilllack the discipline teacher.The theory used is Supardi theory is the ability and success of teachers in carrying outlearning tasks shown by the indicators. In this study the authors use a qualitative descriptivestudy was conducted in 003 Elementary School District of PulauPadang Singingi RegencyKuantanSingingidistrik.In the data collection be conducted key informant interviews, theleadershif teacher. Analysis of data the performance of teachers certified in ElementarySchool 003 Pulau Padang then analyzed what are the factors that affect the performance ofcertified teachers who are supported by interviews conducted by the researcher then bededuced.The results of the research showed that the performance of teachers certified inElementary School 003 Pulau Padang optimal because it is supported by good leadearshipofthe principal and also a good team work of all the teachers.Then the limiting factor is theperformance of teachers certified individual factors, namely the teachers have not been ableto develop personal skills, system factors, namelyschool facilities are not yet complete..Keywords: Performance, Certification